Factor structure of Pre‐Loss Grief‐12 in caregivers of people living with dementia. Issue 1 (8th July 2022) - Park, Juyoung; Levine, Hannah; Galvin, James E.
Abstract: Introduction: The objective was to develop and refine a version of the Prolonged‐Loss Grief‐12 (PG‐12) specific to caregivers of people living with dementia. Confirmatory factor analysis (CFA) was performed to test the fit of the data from the caregivers and to assess the factor structure of the PG‐12 in order to evaluate pre‐loss grief accurately by identifying relevant items and eliminating items that are not appropriate for caregivers of persons with dementia. Methods: A total of 699 eligible caregivers of persons living with dementia (PLWDs) were recruited through relevant dementia associations and organizations. The e‐mail for recruitment provided potential participants with information about the study and detailed instructions on how to participate by following a link to the online survey. Secondary analysis was based on the survey data. CFA was conducted via the Full Information Maximum Likelihood estimation method to test the unidimensional model of PG‐12 in the study population. Standard procedures were used to establish the parameters in the factor loading, factor variance‐covariance, and uniqueness matrices. Results: The initial model was modified to develop a better fitting model and to detect misfitting parameters in the PG‐12 by deleting irrelevant items for the PLWD's caregiver. The adjusted dementia‐specific 10‐item version (PG‐10‐D) had significantly improved fit indices. An overall assessment of fit indicated that the model adequately approximated the data. Factor loadings ranged from 0.53 to 0.85. Discussion: We found that the dementia‐specific, unidimensional PG‐10‐D, modifying the original PG‐12, may be useful and parsimonious in assessing and quantifying pre‐loss grief in dementia caregivers. Future studies are needed to further test its validity and reliability. Highlights: First study to evaluate a dementia‐specific 10‐item version (PG‐10‐D) of the Prolonged‐Loss Grief‐12 (PG‐12). PG‐10‐D is useful in assessing and quantifying pre‐loss grief in caregivers. PG‐10‐D could be an early identifier of caregivers at risk for pre‐loss grief. PG‐10‐D could be the standard measure for effective intervention for caregivers.